Jamnia After Forty Years - Lewis, Jack Pearl (Hebrew Union College annual, 1999)
Though technical discussions of the canon of Scripture have abandoned the view widely held at mid-century that the canon was closed at the Council/Synod of Jamnia, the hypothesis is still expounded in numerous standard reference works as well as in many expositions on the Internet. This paper updates and expands a study of forty years ago, noticing that Jacob Neusner, his students, and others have made available in English the traditions of the sages of the Yavneh period. A summary of traditions concerning Yavneh and the concerns of its scholars is offered to make the more obvious that they contain nothing of the closing of the canon at a Council of Jamnia. It is recognized that no contemporary sources exist and that the traditions may be colored by later developments. Consideration is given to the terminology used in describing Yavneh gatherings, contending that the terms "council" or "synod" are unsuitable for them. The thesis of the author is that the texts (whether taken historically or legendarily) do not support the Council of Jamnia hypothesis. While the earlier study dealt only with the question of the closing of the canon, the present study shows that the traditions also do not support hypotheses that the text of Scripture was fixed or that the final break between Jews and Christians took place at the alleged council.